German S1 guidelines for the diagnosis and treatment of perianal dermatitis (anal eczema). (29th May 2020) - Weyandt, Gerhard; Breitkopf, Claudia; Werner, Ricardo Niklas; Zidane, Miriam; Furtwängler, Alex; Jongen, Johannes; Rothhaar, Alex; Schaefer, Daniel; Lenhard, Bernhard
Summary: Perianal dermatitis (anal eczema, perianal eczema) is one of the most common proctological conditions. It may occur as a sequela or a presenting symptom of various proctological, dermatological, allergic or pathogen‐induced disorders. The three main types of anal eczema are irritant‐toxic, atopic and allergic contact dermatitis. Adequate and successful treatment requires a comprehensive diagnostic workup to determine disease etiology and includes treatment/elimination of causative factors as well as nonpharmacological interventions (avoidance of aggravating factors). In addition, adjuvant topical anti‐inflammatory and/or specific symptomatic treatment may be required. The present guidelines contain recommendations for the diagnostic and therapeutic management of perianal dermatitis. Target users of these guidelines are clinicians in the fields of dermatology and proctology, as well as all other specialties involved in the management of patients with perianal dermatitis, both in hospital and office‐based settings.